2018
DOI: 10.1111/1751-2980.12648
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of golimumab in biologically experienced and naive patients with active ulcerative colitis: A real‐life experience from two Italian IBD centers

Abstract: Our real-life experience showed that CR decreased over time and was achieved by almost one-third of the cohort at the last follow-up visit. Golimumab showed an overall favorable safety profile and the results were not different between biological naive and experienced patients. Future research is needed to confirm our results and to identify criteria to select patients most likely to respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 19 publications
8
13
0
Order By: Relevance
“…Regarding colectomy and hospitalisation rates, both were low and similar to those in other real-world studies 27 . Other studies have also found a lower rate of surgery in naive patients 6,18 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Regarding colectomy and hospitalisation rates, both were low and similar to those in other real-world studies 27 . Other studies have also found a lower rate of surgery in naive patients 6,18 .…”
Section: Discussionmentioning
confidence: 84%
“…However, at long-term (2 years) biological-naive patients have similar percentages of discontinuation than anti-TNF previously exposed patients 5 . An Italian study, that included 59 UC patients that received golimumab with a mean treatment duration of 52 weeks, neither found differences between naive and experienced patients 18 . This finding has been verified recently 19 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most of these studies were performed at tertiary referral centres and there are few realworld data on long-term outcomes. To the best of our knowledge, only four reports of the 52-week clinical remission rate with golimumab have been published [12][13][14][15] and only one of them gave detailed information on the long-term effect on endoscopic or biochemical activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrates that third-class biologic therapy is a feasible, effective, and safe option in Crohn's disease. It is well established that the number of prior treatments is negatively associated with therapeutic success [29,31,32], and that biologic-naïve patients have a substantially higher likelihood of a response to treatment in inflammatory bowel diseases (IBDs) [17,[33][34][35][36][37]. Until a few years ago, our therapeutic armamentarium in IBD was limited to TNF-alpha inhibitors only, but since then it has expanded to include anti-integrins, IL12/23 blockers, and JAK inhibitors.…”
Section: Discussionmentioning
confidence: 99%